A utilização da desapropriação para fins urbanísticos em imóveis abandonados: um estudo de caso em Salvador/Ba - SANTOS, Bruno Oliveira dos (2017)
The present study had as objective to analyze the degree of use of the legal institute of the expropriation for urban planning purposes by the Municipal Public Power of the City of Salvador / BA, in relation to the abandoned properties located in its territory, in the period understood from 1988 to 2016. Therefore, a methodological approach was chosen, characterizing the case study, using the following techniques of operationalization: bibliographic research, documentary and geoprocessing. Also, in order to analyze and interpret the data, the following categories of analysis were extracted from the theoretical foundation: space, territory, place and social function of the city. The sources used were the databases of the census tracts of the Brazilian Institute of Geography and Statistics (IBGE), which classifies abandoned properties (not occupieds) as “vacant permanent unoccupied private households”, as well as research into the express prediction of expropriation for urban purposes in the urban regulator plans of Salvador, during the period under consideration, being used as a parameter the Urban Regulator Plan of the City of São Paulo in 2014. Thereby, we can verify that this institute was only expressly foreseen in the urban regulator plans of Salvador for the years 2004, 2008 and 2016, considering that during the period of validity of these plans, there was a significant increase in the number of abandoned properties. Subsequently, the data were georeferenced in the cartographic network of the city, where we observed a significant increase during the analyzed period of abandoned properties in the most valued areas of the city, increasing real estate speculation in such locations, as well as a significant increase of abandoned properties in poor areas of basic infrastructure. Finally, among the research findings, we find that the legal institute of gratuitous levy of vacants properties is the most practical and less costly solution to publics coffers than expropriations.